The Relationship Between Business Planning and Business Performance Towards Microbusiness - Bacroya, Kayte Jassen; Ampoeda, Daiserie; Andilab, Mark Lloyd Anthony; Ardenes, Laiza; Gonzales, Metonia; Becaro- Lapiz, Jishanis Mae (Journal of Interdisciplinary Perspectives, 2025)
This study investigates the relationship between business planning and business performance among microbusinesses in Cabanglasan, Bukidnon. Business planning serves as a strategic tool to enhance operational effectiveness by mitigating risks, ensuring precise project execution, and optimizing the use of financial resources. Applying a quantitative research design, data were collected from 79 registered sari-sari store owners using structured questionnaires focused on planning-related practices. Descriptive statistics and Pearson correlation analysis were used to assess the extent to which planning components influence performance indicators. The results revealed that microbusinesses that practice strong risk mitigation strategies, well-organized projects, and disciplined financial resource management report notable improvements in profitability, customer satisfaction, and business continuity. Risk mitigation had the most significant influence on overall performance. Challenges were observed in the adoption of digital tools and in access to financial support, which limit further gains. The findings emphasize the need to strengthen local training programs, resource-allocation strategies, and support systems tailored to the realities of microenterprises. This study provides policymakers, regional development agencies, and educators with meaningful insights to promote sustainable growth in rural microbusiness sectors.